In-depth transcriptome unveils the cadmium toxicology and a novel metallothionein in silkworm. (June 2021) - Liu, Yue; Yang, Chengfei; Sun, Le; Wang, Aoming; Lan, Xinhui; Xu, Wei; Liang, Yan; Ma, Sanyuan; Xia, Qingyou
Abstract: Heavy metal pollution has gradually become a major global issue. It is so far reaching in part because heavy metals are absorbed by soil and affect almost all species via ecological cycles. Silkworms ( Bombyx mori ) are poisoned by heavy metals through a soil-mulberry-silkworm system, which inhibits larval growth and development and leads to a decrease in silk production. In the present study, we performed transcriptome sequencing of larval midgut with cadmium exposure to explore the toxicological mechanism of heavy metal, and found that the following potential pathways may be involved in cadmium infiltration: endocytosis, oxidative phosphorylation, and MAPK signaling. Moreover, we identified a novel metallothionein in silkworm, which is inhibited by cadmium exposure and able to improve heavy metal tolerance in B. mori cell lines and Escherichia coli . We also generated a transgenic silkworm strain overexpressing metallothionein and the result showed that metallothionein observably enhanced larval viability under cadmium exposure. This study used RNA sequencing to reveal a mechanism for cadmium toxicology, and identified and functionally verified BmMT, offering a new potential heavy metal-tolerant silkworm variety. Graphical abstract: Image 1 Highlights: Cadmium toxicology analysis in silkworm by midgut transcriptome. Identification and functional exploration of a novel silkworm metallothionein gene. Generation of a transgenic silkworm strain with high Cd tolerance.